From Joints to the Heart: An Integrated Perspective on Systemic Inflammation - Diana Elena Cosău; Irina Iuliana Costache Enache; Alexandru Dan Costache; Ionuț Tudorancea; Codrina Ancuța; Dragomir Nicolae Șerban; Codruța Minerva Bădescu; Cătălin Loghin; Ionela Lăcrămioara Șerban (Life)
Background: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease which predominantly affects joints, but it can also lead to significant extra-articular complications, particularly cardiovascular disease (CVD). Chronic systemic inflammation promotes endothelial dysfunction and accelerates atherosclerosis, increasing cardiovascular risk. Methods: Current data were analyzed to explore the mechanisms between RA and CVD, focusing on systemic inflammation, pro-inflammatory cytokine patways (IL-1, IL-6, TNF, and JAK-STAT), and their interactions with traditional cardiovascular risk factors. Recent studies and clinical guidelines were reviewed to highlight gaps and advances in risk assessment and management. Results: Persistent disease activity and the presence of autoantibodies significantly increase cardiovascular risk in RA contributing to atherosclerosis and major cardiovascular events. Data also suggest that anti-inflammatory treatments, including methotrexate and biologic agents, may lower this risk. Conclusion: This review highlights the pathophysiological mechanisms between RA and CVD, and the need for early diagnosis and active monitoring to identify and assess cardiovascular risk. A multidisciplinary approach, involving rheumatologists and cardiologists is essential for optimizing cardiovascular risk management and improving patient outcomes. Optimization of cardiovascular risk management strategies in patients with RA should be an essential component of current medical practice, with the main goal of reducing morbidity and mortality from cardiovascular complications.